2007
DOI: 10.1300/j084v19n01_09
|View full text |Cite
|
Sign up to set email alerts
|

Gendered Policies and Practices that Increase Older Men's Risk of Elder Mistreatment

Abstract: We aim to detail some of the ways that social policy and gendered practices put older men at risk of elder mistreatment. Research on the abuse and neglect that older adults experience has often focused on the characteristics of the victims and the dynamics within families, emphasizing factors such as the likelihood of an intergenerational cycle of violence, substance abuse and dependency, and older men's financial status as key risks in elder abuse. The effect on men from this type of analysis is that elder mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The Ecological Model allows for an integrated and holistic approach to the prevention of violence, through the framework of nested systems linking elder abuse to broader social issues, and taking into account different levels of interactions (individual, relationship, community and society) [ 135 ]. Specifically, individual prevention strategies can promote attitudes, beliefs, and behaviours that may prevent elder abuse [ 58 ], but it is also crucial to analyse the abuse of older men as a societal problem, as well as an individual and family question [ 71 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ecological Model allows for an integrated and holistic approach to the prevention of violence, through the framework of nested systems linking elder abuse to broader social issues, and taking into account different levels of interactions (individual, relationship, community and society) [ 135 ]. Specifically, individual prevention strategies can promote attitudes, beliefs, and behaviours that may prevent elder abuse [ 58 ], but it is also crucial to analyse the abuse of older men as a societal problem, as well as an individual and family question [ 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is also important to clarify that in the discussion we propose explanations of results which are male specific but also further explanations related to elder abuse in general, thus concerning both men and women as victims of mistreatment. In the final analysis, the reasons leading to male or female elder abuse seem indeed more similar than different with regard to some aspects, and generally they relate to older age conditions and to violence against vulnerable people [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…The aim of our study is indeed mainly to highlight the existence of abuse also towards men, by suggesting a possible (although incomplete) portrait of male abuse, without providing specifically peculiarities of abused men with regard to female gender, but however with some support from findings on female abuse. It is furthermore to keep in consideration that, previous authors, indicated how both adult men and women are victims of mistreatment [ 57 ], and the related similar reasons generally pertain to vulnerable conditions in late life [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…* Hence, viewed from a broader multivariate perspective, it becomes clear that health risks commonly attributed to men in the aggregate may not apply to all men equally or even to the same man at all times throughout his life. 17,37,44,46,53,54,59 In a similar vein, another critical mediator of well-being that recently has come into sharp focus centers on disenfranchised status, given that socially marginalized men (eg, low SES, ethnic and sexual minorities) are affected disproportionately by gendered health disparities. 8,11,14,19,21,30,52 One frequently overlooked aspect of marginalization involves incarceration, which represents a growing health risk for increasing numbers of predominantly ethnic minority men.…”
Section: Beyond Main Effectsmentioning
confidence: 99%